"The Journey to Happiness": A Study on the Development of Farmers' Co-operatives through Innovative Benefit-Linking Mechanisms to Help Farmers: -- Based on the Research of Farmers' Co-operatives in 9 Counties of Jiangxi Province - Xiao, Rong; Cao, Wenqi; Xu, Ruomiao; Li, Lejing; Liu, Yang (Transactions on Social Science, Education and Humanities Research, 2024)
The report of the 20th Party Congress stresses that rural revitalisation lies in industrial prosperity, and the mechanism of cooperatives is an important hand for rural prosperity, but the existing benefit linkage mechanism of farmers' cooperatives is not sound, i.e., the ability to create benefits is weak; the effect of benefit incentives is not obvious; the distribution of benefits is unreasonable; and the benefit linkage is not standardised. Does the above benefit linkage mechanism affect the performance of co-operatives? How to build a reasonable and effective benefit linkage mechanism to improve the performance of co-operatives? Based on the research on farmers' cooperatives in nine counties of Jiangxi Province, we found that the "four-in-one" mechanism, i.e., production and marketing, shareholding, credit and risk control, can effectively solve this problem and provide an effective impetus for the realisation of common wealth.